Galactomannan antigen and Aspergillus antibody responses in a transplant recipient with multiple invasive fungal infections. Issue 2 (April 2015) - Dupont, D.; Geffriaud, T.; Boibieux, A.; Rimmele, T.; Picot, S.; Persat, F.
Abstract : Introduction: We report Aspergillus antigen and antibody responses in a case of multiple invasive fungal diseases. Case presentation: The patient, a double‐lung transplant recipient, had candidaemia and invasive pulmonary aspergillosis with cerebral involvement. The follow‐up of the serum Aspergillus galactomannan antigen by ELISA showed a level increase that correlated with the patient's aggravation. It was retrospectively completed by kinetics analysis using different anti‐ Aspergillus antibody assays (ELISA and Western blotting). Conclusion: A balance between the Aspergillus antigen and anti‐ Aspergillus antibodies was shown using different anti‐ Aspergillus antibody assays. The results of these two antibody techniques appeared rather congruent.